Feminist Collections, v.12, no.3 (spring 1991) - (:unkn) unknown (My University, 1991)
Subtitle: A Quarterly of Women's Studies Resources. 30p.
BOOK REVIEWS: Women and the Discourses of Literacy, by Joan Sullivan. Working in a Fragmented World: Possibilities for Postmodern Feminism, by Susan Koenig. FEMINIST VISIONS: Using Internet to Reach Libraries, Part I, by Susan Dentinger. CANADIAN GOVERNMENT CUTBACKS TO FEMINIST PERIODICALS: by Philinda Masters. FEMINIST PUBLISHING: Two new presses, a preview of the Fifth International Feminist Bookfair, and a new organization for multicultural writers and publishers. ARCHIVES: The Women's Archives Project at Rutgers and the Canadian Women's Movement Archives. NEW REFERENCE WORKS IN WOMEN'S STUDIES: A dictionary of British feminists, biographical guides to women writers in English, to women rulers, and to women in psychology, bibliographies on women outdoors, sex differences in learning, women in higher education, American women's poetry, Ohio State University resources on African and African American women writers, seventeenth century women's literature, and violence against women in Latin America and the Caribbean, guides to women's studies programs and centers, to graduate work in women's studies, and to women travellers, a handbook on women in film, an annual review on women's health issues, a statistical resource on American women, a compendium on AIDS and women, a new index in women's studies, and two sources for quotations by women. (Reviewed by Susan Searing.) PERIODICAL NOTES: New periodicals on Black lesbians, women business owners, art, abortion and health activism, women's culture, recovery, African development, and grassroots work in Zimbabwe. Special issues of periodicals on the silencing of writing, on Toni Morrison, and on aesthetics and feminism. Transitions: WOMEN'S ART is the new name for WOMEN ARTISTS SLIDE LIBARY JOURNAL, and BISEXUALITY ceases temporarily. (Compiled by Linda Shult.) ITEMS OF NOTE: A poster on sex discrimination laws, a list of women and minorities in doctoral programs, a report on older graduates of women's colleges, a "feminization of power" strategy kit, a tool for evaluating higher education salaries, a position statement, a pamphlet for international students, and other resources on campus sexual harassment, a packet of resources for work to end violence against women, posters on sexual assault, a survey on first-year college students' attitudes, a new multicultural collection of films, a mailing list directory, a listing of Milwaukee women's organizations, and a directory of scholars at UCLA. (Compiled by Ingrid Markhardt.) BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews